Kavango music - Dargie, David (International Library of African Music, 2013)
From 1979 to 1988 I conducted a number of church music composition workshops in Kavango, among the various population groups there. Because the workshop participants were very much in touch with their traditional music, the music which they produced in those workshops provided excellent material for a study of Kavango musical style. The workshop recordings, together with recordings of traditional instrumental songs made during those trips, provide the data that enabled the writing of this article, the first attempt to document analytically the elements of Kavango music. Much of the material in the preliminary section is based on the books Fleisch and Mohlig (2002) and Gibson et al. (1981).
Keywords: African Music